0145 Pre-Sleep Cognitive Arousal Decreases Following a 4-Week Introductory Mindfulness Course. (27th May 2020) - Hassirim, Z; Lim, E C; Lo, J C; Lim, J
Abstract: Introduction: Mindfulness-based training has shown potential in reducing anxious and ruminative thoughts before sleep, and improving sleep quality. However, traditional 8-week programs have limited acceptability and uptake. In this study, we aimed to test the effects of a short introductory mindfulness training course on pre-sleep arousal and sleep quality. Methods: Enrollees in a 4-week Mindfulness Foundation Course were invited to participate in the study and were allocated to one of two groups: intervention (N = 57) and waitlist control (N = 39). 101 participants enrolled in the experiment and 96 completed the protocol (mean(sd) age = 49.5(1.5), 56 female). Participants completed the Pittsburgh Sleep Quality Inventory (PSQI) and the pre-sleep arousal scale (PSAS), and were monitored by actigraphy for a week at baseline and post-intervention. To test the effect of the intervention, outcome variables were subjected to repeated-measures ANCOVA with group as a between-subject variable, and age, gender, and years of education as covariates using intent-to-treat analysis. Results: PSQI scores improved across both groups (treatment: t56 =4.25, p<.001, mean(sd) = 6.93(3.25)); waitlist: t38 =3.27, p=.002, mean(sd) = 7.15(3.55)); however, there was no significant interaction between group and time. There was a significant group by time interaction in the cognitive arousal subscale of the PSAS (F1, 90 =4.71, p=.03), Post-hoc tests revealed a significant decrease in the treatment but not the waitlist group (treatment: t50 =3.17, p=.001; waitlist: t30 =0.20, p=.84). The decrease in cognitive arousal correlated with the decrease in PSQI scores in the treatment group only (r =.3, p=.007). Finally, a statistically significant interaction favoring the treatment group was also observed in actigraphically measured WASO (F1, 82 =6.18, p=0.015). Conclusion: The study suggests that a 4-week introductory mindfulness course has moderate effects on reducing cognitive arousal prior to sleep, and that these effects are correlated with improvements in subjective sleep quality. Support: This study was funded from a STaR investigator grant (NMRC/STaR/0015/2013) and the National Research Foundation (Singapore) Science of Learning Grant (NRF2016-SOL002-001).